Relationship Between Selection Procedures for Higher Education and Academic Performance of Students, Based on a Classification Using Fuzzy Sets [Relación Entre Los Procedimientos de Selección a la Educación Superior y el Desempeño Académico de Los Estudiantes Con Base en Una Clasificación Mediante Conjuntos Difusos] - Palominos-Villavicencio, F; Canete-Arratia, L; Diaz-Munoz, H (Centro de Informacion Tecnologica, 2018)
This paper explores the relation between the indicators of academic performance and the data relatives to the admission procedures of freshman students in four university careers belonging to a traditional state university of the metropolitan region of Chile, in the cohorts 2004 to 2014. The study was mainly developed around the indicator called effectiveness and weighted average accumulated of the grades obtained by the students. These were analyzed using a classification based on in fuzzy sets that were built employing membership functions empirically defined, based on experience. The statistical calculations carried out in the study do not show conclusive evidence about that the selection procedures and the admission tests are correlated with variables associated with the success and academic performance of the students in their careers. © 2018. Formación Universitaria. All Rights Reserved.